Integrating Oral Health into Health Professions School Curricula. Issue 1 (31st December 2022) - Gill, Stephanie A.; Quinonez, Rocio B.; Deutchman, Mark; Conklin, Charles E.; Rizzolo, Denise; Rabago, David; Haidet, Paul; Silk, Hugh
ABSTRACT: Oral health is essential to human health. Conditions associated with poor oral health involve all organ systems and many major disease categories including infectious disease, cardiovascular disease, chronic pain, cancer, and mental health. Outcomes are also associated with health equity. Medical education organizations including the Association of American Medical Colleges and National Academy of Medicine recommend that oral health be part of medical education. However, oral health is not traditionally included in many medical school, physician assistant, or nurse practitioner curricula. Several challenges explain this exclusion including lack of time, expertise, and prioritization; we therefore provide suggestions for integrating oral health education into the health professions school curriculum. These recommendations offer guidance for enhancing the oral health curriculum across institutions. We include key organizational and foundational steps, strategies to link oral health with existing content, and approaches to achieve curricular sustainability.